2022
DOI: 10.3390/molecules27093019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Characterization of Selective Cannabinoid CB2 Receptor Agonists: Biological Evaluation against Neuroblastoma Cancer Cells

Abstract: 1,8-naphthyridine-3-carboxamide structures were previously identified as a promising scaffold from which to obtain CB2R agonists with anticancer and anti-inflammatory activity. This work describes the synthesis and functional characterization of new 1,8-naphthyridin-2(1H)-one-3-carboxamides with high affinity and selectivity for CB2R. The new compounds were able to pharmacologically modulate the cAMP response without modulating CB2R-dependent β-arrestin2 recruitment. These structures were also evaluated for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…We have reported a dose-dependent reduction in melanoma and CRC cell viability when exposed to URB447. These findings are in line with recent studies using a new CB2 agonist reporting the same trend [ 25 ]. We observed that this decreased cell viability is partly mediated by tumor cell apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…We have reported a dose-dependent reduction in melanoma and CRC cell viability when exposed to URB447. These findings are in line with recent studies using a new CB2 agonist reporting the same trend [ 25 ]. We observed that this decreased cell viability is partly mediated by tumor cell apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Pharmacological activation or upregulation of CB1R and/or CB2R inhibits tumor growth and metastasis in vivo, attenuated proliferation, migration/invasion, and angiogenesis, and induced apoptosis in vitro through inhibition of extracellular signal-regulated kinase (ERK), protein kinase B (PKB)/AKT, cAMP/protein kinase A (PKA), c-Jun N-terminal kinase (JNK), MAPK p38, nuclear factor kappa B (NF-κB), and/or vascular endothelial growth factor (VEGF) signaling pathways, in various human cancers, including glioma [ 144 , 145 ], leukemia [ 146 , 147 , 148 ], multiple myeloma [ 149 ], neuroblastoma [ 150 ], breast [ 151 , 152 , 153 , 154 ], cervical [ 105 ], colorectal [ 110 , 155 , 156 , 157 ], endometrial [ 158 ], hepatocellular [ 159 ], intestinal [ 108 ], non-small-cell lung [ 160 , 161 ], prostate [ 162 , 163 ], and thyroid cancers [ 164 ]. The antitumorigenic and/or proapoptotic effects can be blocked by inhibition and/or knockdown of CB1R and/or CB2R [ 144 , 145 , 146 , 149 , 152 , 153 , 155 , 160 , 162 , 164 ].…”
Section: Ecs and Cancermentioning
confidence: 99%